Identifying the Key Role of Pyridinic‐N–Co Bonding in Synergistic Electrocatalysis for Reversible ORR/OER - Wang, Xue‐Rui; Liu, Jie‐Yu; Liu, Zi‐Wei; Wang, Wei‐Chao; Luo, Jun; Han, Xiao‐Peng; Du, Xi‐Wen; Qiao, Shi‐Zhang; Yang, Jing (Advanced materials (Weinheim), 2018)
For many regenerative electrochemical energy‐conversion systems, hybrid electrocatalysts comprising transition metal (TM) oxides and heteroatom‐doped (e.g., nitrogen‐doped) carbonaceous materials are promising bifunctional oxygen reduction reaction/oxygen evolution reaction electrocatalysts, whose enhanced electrocatalytic activities are attributed to the synergistic effect originated from the TM–N–C active sites. However, it is still ambiguous which configuration of nitrogen dopants, either pyridinic or pyrrolic N, when bonded to the TM in oxides, predominately contributes to the synergistic effect. Herein, an innovative strategy based on laser irradiation is described to controllably tune the relative concentrations of pyridinic and pyrrolic nitrogen dopants in the hybrid catalyst, i.e., NiCo2O4 NPs/N‐doped mesoporous graphene. Comparative studies reveal the dominant role of pyridinic‐NCo bonding, instead of pyrrolic‐N bonding, in synergistically promoting reversible oxygen electrocatalysis. Moreover, density functional theory calculations provide deep insights into the corresponding synergistic mechanism. The optimized hybrid, NiCo/NLG‐270, manifests outstanding reversible oxygen electrocatalytic activities, leading to an overpotential different ΔE among the lowest value for highly efficient bifunctional catalysts. In a practical reversible Zn–air battery, NiCo/NLG‐270 exhibits superior charge/discharge performance and long‐term durability compared to the noble metal electrocatalysts. An innovative strategy based on laser irradiation is developed to selectively regulate relative contents of pyridinic and pyrrolic nitrogen in NiCo2O4/N‐graphene hybrids. Strong chemical bonding forms between nitrogen and cobalt, and pyridinic‐NCo bonds, instead of pyrrolic‐NCo bonds, are identified to predominantly contribute to synergistic catalysis, leading to substantially enhanced oxygen electrocatalytic activities, outperforming a combination of benchmark noble metal catalysts.